Pengaruh Penerapan Good Corporate Governance terhadap Profitabilitas dengan Kualitas Audit sebagai Variabel Moderasi - Evi Dora Sembiring; Deti Susilawati; Firli Agusetiawan Shavab; Fiesty Utami (FEB Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to determine the effect of Audit Committees, Independent Commissioner, and Institutional Ownership on Profitability. This study also determines whether Audit Quality can moderate the influence of the Audit Committee, Independent Commissioners, and Institutional Ownership on Profitability. The samples are 44 companies from the Chemical Sub-Sector listed on the Indonesia Stock Exchange for 2018-2021 period. The research method used is quantitative research with secondary data collection techniques. The analysis technique uses multiple linear regression analysis and moderated regression analysis (MRA) and the analysis tool used is SPSS 26. The results showed that the Audit Committee had a significant positive effect on profitability, the Independent Commissioner had a negative effect on profitability and institutional ownership did not affect profitability. Audit Quality can moderate and strengthen the influence of the Audit Committee and Institutional ownership on profitability, but Audit Quality does not moderate the influence of independent commissioners on profitability.